Impact of Leadership Styles of Principals on Teacher Educants: A Study of Colleges of Education in Northern Ghana - Iddrisu Sulemana; Shanunu Zakaria; Alhassan Imoro Nuhu (Noyam Journals, 2020)
The study examined the impact of leadership styles of Principals of Colleges of Education in Northern Ghana. A descriptive survey research design was used together with a convenient sampling technique. Using a structured questionnaire, data were gathered from one hundred (100) Teacher educants and Principals from the Colleges of education in Northern Ghana. The Likert rating scale was adopted to indicate the extent of agreement or disagreement. The findings indicated that the majority of the respondents agreed their principals have a good relationship with teacher educants. The personality traits exhibited by the Principals in the Colleges of Education in Northern Ghana varied and each of the leadership styles exhibited exerted positive but insignificant effect on teacher educants performance. It is being recommended that to promote teacher educants satisfaction at the workplace, principals must create congenial climate in their respective colleges to ensure that teacher educants can share and freely express their opinions. Pre-service and in-service training programmes must be organized periodically to improve performance.